Operasi Tangkap Tangan (OTT) Tinjauan Berdasarkan KUHAP Dan Undang Undang Nomor 30 Tahun 2002 Tentang Komisi Pemberantasan Korupsi (KPK) - Frisca Tyara M Fanhar (Faculty of Law, Universitas Lampung, 2020)
The ambiguity regarding the mechanism and limits of the authority of the arresting operations carried out by the corruption eradication commission raises public assumption that the authority exercised by the corruption eradication commission has violated the law and even violated human rights, namely taking arbitrary actions (unprocedure).The problem in writing this study is How can the legal force of the operation of the corruption eradication commission arrest if viewed from the aspect of the Criminal Procedure Code and Law Number 30 of 2002 Concerning the Corruption Eradication Commission? What are the criteria for an alleged crime using a arrest operation? What is the ideal way for the Corruption Eradication Commission to carry out arrest operations? This study uses a Normative and Empirical Juridical approach. Normative research is carried out on matters that are theoretical principles of law, whereas an empirical approach is carried out to study law in reality. The results of the study found that legal force of the act of arrest operations of the corruption eradication commission if viewed from the aspect of the Criminal Procedure Code and Law Number 30 of 2002 Concerning the Corruption Eradication Commission actually the act of arrest operations of the corruption eradication commission does not have a strong legal basis from the juridical aspects of criminal law. problem of violating the principle of due processof law Criteria for Alleged Crime Using a hand arrest operation due to the type or quality of the target of corruption is not a simple crime and therefore the need for a hand arrest operation, and ideally the commission of asan corruption In carrying out arrest operations, it is necessary to have a good case administration system starting from the stage of collecting data and information that is based on an accurate and reliable source of information, after that conducting an investigation in accordance with the standard operating procedures that have been determined then at the execution stage such as conduct monitoring, undercover, tapping and then the operation of arresting the authority must be in accordance with the legislation. The suggestion that can be done is that the legal basis for Operation of Catching Hands must be immediately included in the article instrument in the corruption eradication commission law so that its authority is not at issue